Enhanced thermal conductivity of alumina nanoparticle suspensions by femtosecond laser irradiation. (April 2017) - Ha, J.; Seo, Y.; Choi, T.-Y.; Kim, D.
Highlights: The thermal conductivity, k of alumina nanofluid was enhanced by laser irradiation. The laser stabilization process (low laser fluence) enhances the colloidal stability. The laser fragmentation process (high laser fluence) reduces the particle size. By combining the two processes, k was significantly enhanced up to 38% at 1 wt%. The enhancement of k is due to the enhanced stability and reduced particle size. Abstract: This work reports significant enhancements over the Hashin-Shtrikman upper bound, by means of femtosecond laser irradiation, of thermal conductivity of alumina nanoparticle suspensions dispersed in water. By adjusting laser parameters, the applied femtosecond laser irradiation could enhance the colloidal stability of the suspension and reduce the size of nanoparticles. The thermal conductivity and zeta potential of the suspensions were measured before and after the laser-induced stabilization and fragmentation processes. When the laser stabilization and laser fragmentation processes were combined, the thermal conductivity of the suspension increased up to about 40% compared to the thermal conductivity of the base fluid at 1 wt%. This laser technique demonstrates a strong potential to produce nanofluids with high thermal conductivity and colloidal stability.